Airway reactions and emergence times in general laryngeal mask airway anaesthesia: A meta-analysis. Issue 2 (February 2015) - Stevanovic, Ana; Rossaint, Rolf; Fritz, Harald G.; Froeba, Gebhard; Heine, Joern; Puehringer, Friedrich K.; Tonner, Peter H.; Coburn, Mark
Abstract : BACKGROUND: Desflurane's short emergence time supports fast track anaesthesia. Data on the rate of upper airway complications and emergence time when desflurane is used with laryngeal mask airway (LMA) are controversial and limited. OBJECTIVES: To compare recovery time variables and the rates of upper airway adverse events in patients with an LMA undergoing general surgery with desflurane, sevoflurane, isoflurane or propofol anaesthesia. DESIGN: A systematic review and meta-analysis of randomised controlled trials (RCTs). DATA SOURCES: A systematic search for eligible RCTs in Embase (Elsevier) and in PubMed (National Library of Medicine) databases up to September 2013. ELIGIBILITY CRITERIA: RCTs investigating the rates of cough overall, cough at emergence, laryngospasm, time to eye opening, time to removal of the LMA, time to respond to command and time to state date of birth in patients with an LMA, during emergence from desflurane, sevoflurane, isoflurane or propofol anaesthesia. RESULTS: Thirteen RCTs were included and analysed. We found a strong interstudy variability. There was no difference in the rates of upper airway events between desflurane and sevoflurane or between desflurane and a control group consisting of all the other anaesthetics combined. Comparing desflurane (n = 284) with all other anaesthetic groups ( n = 313), the risk ratio [95% confidence interval (95% CI)] was 1.12 (0.63 to 2.02, P = 0.70). Cough at emergence was only measured in patients receiving desflurane ( n = 148) and sevoflurane ( n = 146): the risk ratio (95% CI) was 1.49 (0.55 to 4.02, P = 0.43). Laryngospasm was rare and there was no significant difference in its incidence when desflurane (n = 262) was compared with all other anaesthetics combined ( n = 289; risk ratio 1.03; 95% CI 0.33 to 3.20, P = 0.96). The times of all emergence variables were significantly faster in the desflurane group than in all other groups. CONCLUSION: When using an LMA, upper airway adverse reactions in association with desflurane anaesthesia were no different from those noted with sevoflurane, isoflurane or propofol anaesthesia. Emergence from general anaesthesia with desflurane is significantly faster than all the other anaesthetics. Due to interstudy variations and the small size of the trials, further large-scale, multicentre studies are required to confirm or refute the results of this meta-analysis. Abstract : Supplemental Digital Content is available in the text